REKRUITMEN PANITIA PENGAWAS PEMILU ADHOC DALAM MENGAWAL KONTESTASI PEMILU TAHUN 2024 - Marzuki, H. M. Wasikin (Bawaslu Provinsi Jawa Barat, 2022)
This paper will look at the recruitment process for the Election Supervisory Committee at the sub district level in the 2024 election as a form of implementation of the Election Supervisory Body Regulation Number 4 of 2022 concerning the third amendment to the Election Supervisory Board Regulation Number 19 of 2017 concerning the formation, dismissal and interim replacement of the Election Supervisory Board. Provincial Election Supervisors, Regency/City Election Supervisory Board, District Election Supervisory Committee, Kelurahan/Village General Election Supervisory Committee, Overseas General Election Supervisory Committee, and Polling Place Supervisors, the role of Adhoc Supervisors as the front guard when conducting general elections simultaneously in 2024, in updating the data it was found that the activities carried out by the Election Supervisory Committee at the sub-district level in West Java Province were optimally pursued starting from the beginning of the election until the election ended.